Pengaruh Level Substitusi Jagung Giling dengan Tepung Kulit Pisang Hasil Fermentasi dalam Pakan Konsentrat dan Imbuhan Zn Biokompleks terhadap Ukuran Linear Tubuh Sapi Bali Jantan Penggemukan - Ratrigis, Yosep; Abdullah, Muhammad S.; Kihe, Johny Nada; Marawali, Aloysius (Animal Agricultura, 2024)
The purpose of this study was to determine the effect of substitution of ground corn with banana peel flour brewed in concentrated feed and Zn Biocomplex on the linear body size of male fattening Bali cattle. The livestock used in this study were 12 male Bali cattle aged between 2-2.5 years with a body weight range of 130.5-173.5 kg. This study used a completely randomized design with 4 treatments and 3 replications, namely P0: Concentrate feed without substitution (Control) + 65 mg Zn biocomplex, P1: Concentrate feed (substitute ground corn in concentrate with KPF 25%) + 65 mg Zn biocomplex, P2: Concentrate feed (substitute ground corn in concentrate with 50% KPF) + 65mg Zn biocomplex, P3 : Concentrate feed (substitute ground corn in concentrate with 75% KPF) + 65mg Zn biocomplex. The parameter studied is the linear size of the body. The results of the statistical analysis showed that the treatment had no significant effect (P>0.05) on the body size of fattening male Bali cattle. It was concluded based on the findings and analysis, feed concentrates including fermented banana peel flour in varying amounts and with the addition of Zn biocomplex had the same effect on the linear body size of fattening Bali bulls during the treatment.